Lack of Association between Hypercholesterolemia and Obesity Status with the Gallstones type among Cholelithiasis Patients at Sanglah General Hospital, Bali, Indonesia - Heru Sutanto Koerniawan (Journal of Global Pharma Technology, 2016)
Introduction: Gallstone disease is still one of the major health problems in the world. It is one of the most common diseases in developed countries associated with many factors. Increased total blood cholesterol, free cholesterol, LDL, triacylglycerol, obesity, and decreased HDL cholesterol levels also play an important role in the pathogenesis of gallstone formation. This study aimed to determine the relationship between hypercholesterolemia and obesity to types of gallstones. Methods: An observational cross-sectional study was conducted at Sanglah General Hospital from January-December 2017. The sample was obtained using consecutive sampling of patients with cholelithiasis that met inclusion and exclusion criteria. Data analysis was done with univariate and bivariate analysis using SPSS version 23 software. The confidence interval was set to 95% and p-value < 0.05 was considered statistically significant. Result: Twenty-six samples were included in this study. Majority of the sample was suffered from gall stone type cholesterol and was performed open cholecystectomy. There was no association found between gall stone type and obesity (p=0.618). In addition, recent findings also suggest no significant differences between gall stone type and total cholesterol status (p=0.211).Conclusion: There is no association between obesity and hypercholesterolemia with gall stone type in cholelithiasis patients.Keywords: Cholelithiasis, Gallstone, Hypercholesterolemia, Obesity.